-3(5s-1)-3=-2(9s+1)-3

Simple and best practice solution for -3(5s-1)-3=-2(9s+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5s-1)-3=-2(9s+1)-3 equation:


Simplifying
-3(5s + -1) + -3 = -2(9s + 1) + -3

Reorder the terms:
-3(-1 + 5s) + -3 = -2(9s + 1) + -3
(-1 * -3 + 5s * -3) + -3 = -2(9s + 1) + -3
(3 + -15s) + -3 = -2(9s + 1) + -3

Reorder the terms:
3 + -3 + -15s = -2(9s + 1) + -3

Combine like terms: 3 + -3 = 0
0 + -15s = -2(9s + 1) + -3
-15s = -2(9s + 1) + -3

Reorder the terms:
-15s = -2(1 + 9s) + -3
-15s = (1 * -2 + 9s * -2) + -3
-15s = (-2 + -18s) + -3

Reorder the terms:
-15s = -2 + -3 + -18s

Combine like terms: -2 + -3 = -5
-15s = -5 + -18s

Solving
-15s = -5 + -18s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18s' to each side of the equation.
-15s + 18s = -5 + -18s + 18s

Combine like terms: -15s + 18s = 3s
3s = -5 + -18s + 18s

Combine like terms: -18s + 18s = 0
3s = -5 + 0
3s = -5

Divide each side by '3'.
s = -1.666666667

Simplifying
s = -1.666666667

See similar equations:

| x/46=-36 | | x-2(y/2x)y=0 | | (11z+8)-(5z-2)= | | 7x+20=14x-5 | | 4(4x-7)+4x=2x-21+16x | | 0=i/8 | | 3(2x+7)=85 | | 5[7-5(6-x)]=7[5(7x-6)+4]-50 | | 0.6x^2+.04x+1=0 | | x^2-3x+k=0 | | -5(21y)= | | 50L+30L/4g/L | | 3p+2q-4pq-2pq= | | 11-3/10x=2 | | -6x=-186 | | 4(5+x)-6(2+x)=4 | | 1/15x+1/18x=11 | | 3/5x^2-x=1/5 | | 10x^2=2w(w+2) | | 4x^2-11x+0=0 | | X*.8=245 | | 0=(x+3/7x-28)-(7/x-4)-(2/7) | | 2ab+b-4ab-5b= | | 2.9x+100=1927 | | 4*.05= | | 18-2/3x=6 | | 4x^2-56x-45=0 | | 4u(u-6)(u+8)=0 | | 0.5(0.1x+0.5)=-0.5 | | -m/6 | | 0.4(0.1x+0.3)=-0.8 | | 10(x-2)+12(x+4)=1 |

Equations solver categories